Lipase-modified pH-responsive microgel-based optical device for triglyceride sensing1. Issue 47 (14th June 2015) - Zhang, Qiang Matthew; Berg, Darren; Mugo, Samuel M.; Serpe, Michael J.
<x xml:space="preserve">Abstract</x> Lipase-modified poly (N-isopropylacrylamide)-based microgels were synthesized, and used to fabricate optical devices (etalons). Triglyceride reacted with lipase to generate fatty acid, which yielded an etalon response.